2013
DOI: 10.4172/2157-7439.1000181
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry and Florescence Analysis of Snap-Nappa Arrays Expressed Using E. coli Cell_Free Expression System

Abstract: We present the analysis of an innovative kind of self-assembling protein microarray, the "Nucleic Acid Programmable Protein Array" (NAPPA), express with the SNAP tag in E.coli coupled self free expression system. The goal is to develop a standardize procedure to analyze the protein protein interaction occurred on NAPPA array combining label free Mass Spectrometry (MS) and fluorescence technology for protein microarray. We employ in the process "Protein synthesis Using Recombinant Elements" (PURE) system. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In this study, we introduced a new application of our previously described NAPPA-based nanoconductometric sensor, (Nicolini et al, 2012a;2012b;Nicolini et al, 2013), which combined with Mass Spectrometry using SNAP arrays (Nicolini et al, 2013) has been extended to cancer studies (Bragazzi et al, 2014a), and in this context has been used to clinically screen patients respondent to TMZ from those refractory to this drug. We performed a positive control (TMZ plus MLH1 protein), a negative control (TMZ plus BRIP1 protein) and a multi-gene experiment (TMZ plus BRIP1&MLH1 being co-expressed), showing that we are able to properly perform pharmacoproteomics tasks, discriminating each protein and drug unique conductance curve as well as their interactions, even in the presence of multi-proteins being immobilized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we introduced a new application of our previously described NAPPA-based nanoconductometric sensor, (Nicolini et al, 2012a;2012b;Nicolini et al, 2013), which combined with Mass Spectrometry using SNAP arrays (Nicolini et al, 2013) has been extended to cancer studies (Bragazzi et al, 2014a), and in this context has been used to clinically screen patients respondent to TMZ from those refractory to this drug. We performed a positive control (TMZ plus MLH1 protein), a negative control (TMZ plus BRIP1 protein) and a multi-gene experiment (TMZ plus BRIP1&MLH1 being co-expressed), showing that we are able to properly perform pharmacoproteomics tasks, discriminating each protein and drug unique conductance curve as well as their interactions, even in the presence of multi-proteins being immobilized.…”
Section: Resultsmentioning
confidence: 99%
“…In the last years, the evolution of the nanobiotechnologies applied to proteins, namely proteomics, both structural and functional and specifically the development of more sophisticated protein arrays, has enabled scientists to investigate protein interactions and functions with an unforeseeable precision and wealth of details (Nicolini et al, 2012a;2012b;Nicolini et al, 2013). Moreover, protein arrays can be coupled with label-free approaches: The so-called cell-free protein arrays (Bragazzi et al, 2014b;Dixon, 2008;Fee, 2013;Hunter, 2009;Spera et al, 2013).…”
Section: Tmz (Brand Namementioning
confidence: 99%
“…Also, the ongoing research in the field of MS coupled with NAPPA and SNAP is giving, as shown recently [26,30], encouraging results in the study of protein-protein interaction, a topic relevant for cancer control. We strongly believe that these efforts can be precious in the field of personalized oncology.…”
Section: Discussionmentioning
confidence: 99%
“…Another innovative approach we developed is given by coupling NAPPA with the SNAP tag E. coli coupled cell-free expression system and Mass Spectrometry (MS) (in particular, the Matrix Assisted Laser Desorption Ionization Time-ofFlight (MALDI-TOF) Bruker Ultraflex) with the goal of implementing a standardized procedure of identification of biomarkers in clinical settings and to analyze the proteinprotein interaction occurred on NAPPA array using label-free technology [26]. We employed the process "Protein synthesis Using Recombinant Elements" (PURE) system, which, due to its high complexity, needs ad hoc in-house developed bioinformatics tools to be analyzed.…”
Section: Figurementioning
confidence: 99%
“…On the light of the sixteen recently published experimental papers, referred in the last section [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], we have successfully completed the feasibility study on Microarray-based Functional Nanoproteomics for an Industrial Approach to Cancer.…”
Section: Introductionmentioning
confidence: 99%